PEMBUKTIAN UNSUR MELAWAN HUKUM DALAM DELIK NARKOTIKA SECARA TERORGANISASI - Mas Diding Eki Sukmadadi; Siswantri Pratiwi; Mardani Mardani (Universitas Stikubank, 2023)
This writing aims to find out the proof of the elements against the law in the case of organized narcotics offences. The method used is normative juridical with the acquisition of secondary data and analyzed based on applicable legal sources. The results obtained in the verdict were correct in stating that the Defendant M. Nofriadi mentioned above, was legally and convincingly proven guilty of committing a criminal act,